Regulators of G protein Signaling (RGS) proteins (version 2019.4) in the IUPHAR/BPS Guide to Pharmacology Database. (2019) - Alqinyah, Mohammed; Bodle, Christopher; Dagher, Josephine Bou
No abstract available